Quality of care in adult patients with inflammatory bowel disease transferring between healthcare providers: multicentre audit. Issue 1 (13th January 2020) - ,; Ahmad, Omer F; Ayubi, Homira; Clough, Jennie; Dart, Robin; Gadhok, Radha; Pannick, Samuel; Parkes, Gareth; Pavlidis, Polychronis; Segal, Jonathan; Sellers, Penelope
Abstract : Background: Inflammatory bowel disease (IBD) predominantly affects young adults at critical socioeconomic periods of their lives. There are no studies examining the process of transfer of care for adult patients with IBD changing healthcare providers. Our aims were to assess the quality of referral information provided when patients with an established IBD diagnosis transfer care between heathcare providers and to assess the impact of referral quality on patient outcome. Methods: Retrospective data pertaining to IBD transfer of care referrals were collected from 16 hospitals across London over a 2-month period. Data were collected on patient demographics, source and content of referral and cross-referenced with an established transfer of care checklist. Patient outcome within the 6 months following transfer was also documented. Results: 154 cases were identified, over half of which transferred due to patient relocation. Details included in transfer letters were in many cases incomplete. In over 70% of cases, the letter came from primary care, including when a tertiary opinion was sought. Although referrals from primary care contained fewer patient data points, there was no association with poor patient outcomes at 6 months. Conclusion: This is the first study examining the quality of transfer of care in adult patients with IBD. We highlighted a significant and underreported issue and found that the majority of referrals were led by primary care. Though the inclusion in the referral of fewer data points was not associated with poor outcomes, we highlighted an area where gastroenterologists might take more responsibility to provide smooth and robust transfer of care.